Clinical and Biochemical Features Used to Classify Type-1 and Type-2 Diabetes: A Scoping Review - Ulagamadesan Venkatesan; Anandakumar Amutha; Ranjit Mohan Anjana; Ranjit Unnikrishnan; Bagavandas Mappillairajan; Viswanathan Mohan (Journal of diabetology, 2024)
Abstract The classification of diabetes into type-1 (T1D) and type-2 (T2D) is a critical step in tailoring effective treatment strategies. This distinction relies on a nuanced evaluation of clinical and biochemical features. While age at diagnosis, autoimmune markers, and beta-cell function are among the crucial clinical parameters, biochemical indicators like C-peptide levels and antibody analyses play a pivotal role. This review comprehensively examines the utility of these features in accurately categorizing individuals into T1D and T2D subtypes, providing valuable insights for clinical practice. This scoping review systematically analyses 32 studies aimed at classifying T1D and T2D using various predictor variables. Clinical parameters including family history of diabetes, age at diagnosis, sex, history of insulin use, percent desirable weight or body mass index, waist, and blood pressure emerge as pivotal diagnostic tools. C-peptide measures, encompassing urinary C-peptide to creatinine ratio (UCPCR), and serum fasting and stimulated C-peptide levels further augment classification. Biochemical markers beyond C-peptide, such as serum level of adiponectin, triglycerides (TG), high-density lipoprotein–cholesterol (HDL-C), low-density lipoprotein (LDL-C), Total cholesterol, fasting and postprandial plasma glucose, and glycated hemoglobin (HbA1c), provide supplementary information for classification. Ketonuria and postglucagon or meal-stimulated C-peptide measurements contribute to nuanced classification, particularly in insulin-treated populations. Antibody analyses, particularly presence of GAD65, Zinc Transporter, and IA2 antibodies, highlight the autoimmune nature of T1D. In conclusion, this scoping review underscores the importance of a comprehensive approach that integrates clinical, biochemical, and immunological markers in accurately differentiating between T1D and T2D in clinical practice.